PENGATURAN DAN PENGELOLAAN PERAMPASAN ASET HASIL TINDAK PIDANA DI INDONESIA DAN AUSTRALIA: Regulation and Management of Asset Forfeiture of Criminal Proceeds in Indonesia and Australia - Daniel Wewo Godo Kana Lo; Maria Silvya E. Wangga (Faculty of Law, Trisakti University, 2025)
Asset forfeiture is often linked to financial smuggling resulting from a crime. The United Nations Convention Against Corruption (UNCAC), encourages its member states to implement asset forfeiture as part of efforts to eradicate corruption and money laundering. Indonesia through Law Number 31 Year 1999 on the Eradication of Corruption, while Australia through the Proceeds of Crime Act 2002. In this issue there are at least 2 (two) problem formulations, namely: 1). How is the Regulation of Asset Forfeiture of Proceeds of Crime in Indonesia and Australia? 2). How is the Management of the Proceeds of Crime Asset Forfeiture in Indonesia and Australia? The normative research method with the nature of descriptive research. The results of the discussion and conclusions are as follows are namely Australia more comprehensively regulates asset forfeiture while Indonesia is still in the form of an Asset Forfeiture Bill. In Indonesia, the management of asset forfeiture proceeds is managed by the Directorate General of State Assets (DJKN) while in Australia by specialized institutions namely the Australian Financial Security Authority (AFSA), Australian Federal Police (AFP), and Confiscated Assets Account (CAA).